Personality Types and Undergraduates’ Learning Styles - Talib, Nabilah Abd; Samsudin, Nur Farhana Athiq; Zin, Norhayati Mohd (Selangor Humaniora Review, 2021)
Each individual has their traits and learning styles that benefit them when learning. Therefore, to ensure the fluidity of the language acquisition process, determining students’ learning styles based on their personalities is essential. Hence, the study is done to determine the relationship between personality types and ESL students’ learning styles. 148 Malaysian undergraduate students from Universiti Selangor were asked to answer the questionnaire. Demographic data were also collected to identify the respondents’ age, gender, ethnicity/race, and native language. This study was conducted based on Myers-Briggs’s MBTI personality test to determine the students’ personality type. At the same time, the C.I.T.E Learning Styles Instrument was used to determine the student’s learning styles. Twenty-five questions with four Likert-like scale options were created. Descriptive data were presented, and Chi-square analysis was used to investigate the relationship between personality types and learning styles. The findings suggested that the predominant personality types among the respondents are introverts. The primary learning style for introverts is solitary learning, while extroverts are social-group learning. The results have shown a significant correlation between personality types and learning styles.